Middle turbinate angiofibroma in an elderly woman - Perić Aleksandar; Baletić Nenad; Cerović Snežana; Vukomanović-Đurđević Biserka (Vojnosanitetski Pregled)
Background. Angiofibromas are histologically benign vascular tumors, originating from the nasopharynx, near by the area of sphenopalatine foramen. These neoplasms occur typically in male adolescents. Reports of primary extranasopharyngeal angiofibromas have appeared sporadically in the literature in English. We present the first case of an elderly woman with tumor arising from the middle turbinate, diagnosed as angiofibroma. Case report. A 63-year-old female presented with left-sided nasal obstruction and epistaxis. Endoscopic evaluation revealed a polypoid mass arising from the anteroinferior portion of the left middle turbinate. Computed tomography (CT) scan showed a soft-tissue opacity that filled the anterior part of the left nasal cavity. After the endoscopic excision of the mass, postoperative pathohistological and immunohistochemical analysis confirmed the diagnosis of an angiofibroma. Two years later, the patient was free of symptoms and without endoscopic evidence of recurrence. Conclusion. Extranasopharyngeal angiofibromas arising from the nasal cavity are extremely rare tumors. Immunohistochemical analysis is very important in all doubtful cases, especially in those with atypical location.